A Taxonomic Study on Zooplankton Fauna of Kiğı Dam Lake (Bingöl-Turkey) - Bulut, Hilal (My University, 2018)
The present study was conducted to determine zooplankton fauna of Kiğı Dam Lake during September2012 and August 2013 seasonally. The zooplankton samples were collected by using plankton net with themesh size of 55µm horizontally and preserved in 4% formaldehyde. Total 22 taxa (16 Rotifera, 4 Cladocera,and 2 Copepoda) were identified in Kiğı Dam Lake. Ascomorpha saltans, Asplanchna priodonta, Brachionusangularis, Cephalodella gibba, Euchlanis dilatata, Kellicottia longispina, Keratella cochlearis, Keratellaquadrata, Lecane luna, Lecane lunaris, Notholca squamula, Polyarthra dolichoptera, Rotaria rotatoria,Synchaeta pectinata, Synchaeta oblonga, Trichocerca capucina from Rotifera species; Bosmina longirostris,Chydorus sphaericus, Daphnia cucullata, Daphnia longispina from Cladocera species; Acanthodiaptomusdenticornis, Cyclops vicinus from Copepoda species are new records for this dam lake. Zooplankton sampleswere consisted of 72.7% Rotifera, 18.2% Cladocera, and 9.1% Copepoda.
Keywords: Biyoloji; Limnoloji; Deniz ve Tatlı Su Biyolojisi